The role of regionalism in the architecture of Santa Maria Assumpta Church by Y. B. Mangunwijaya - Audilia, C; Kurniawan, F (ASCEE, 2023)
Architecture as a science of designing, does not revolve around materials, spaces, and expressing aspirations only. The shape of the building style that changes from time to time shows the response of involvement to the surrounding environment and can be a challenge that may eliminate the characteristics of the place if it is left unnoticed. Regionalism as an approach in architecture becomes a knowledge that can be applied to express the characteristics and values of the region. The Catholic Church in Indonesia is one of the examples that has a connection with the approach, and not just related to the adaptation of local culture so it becomes familiar with the community, but also how it shows the universal church in it. Mangunwijaya, one of the architects in Indonesia, who was also a culturalist, pointed out the use of regionalism in his architectural works. This study aims to determine how far the application of regionalism in one of his works and discover his actions in implementing regionalism. The research used a qualitative approach and collected library data from various sources. The author used descriptive analytic methods in verifying elaborated theories about regionalism in the case study of the Church of Santa Maria Assumpta in Klaten by Y. B. Mangunwijaya. This research shows that the concept of regionalism can also be applied in Indonesia. The research also found the importance of applying regionalism which is not only to display the local characteristics but also to support the needs of the people in church.